2006
DOI: 10.1124/jpet.106.105163
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic and Antioxidant Properties of Caffeic Acid indb/dbMice

Abstract: This study investigated the blood glucose-lowering effect and antioxidant capacity of caffeic acid in C57BL/KsJ-db/db mice. Caffeic acid induced a significant reduction of the blood glucose and glycosylated hemoglobin levels than the control group. The plasma insulin, C-peptide, and leptin levels in caffeic acid group were significantly higher than those of the control group, whereas the plasma glucagon level was lower. Increased plasma insulin by caffeic acid was attributable to an antidegenerative effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(178 citation statements)
references
References 42 publications
7
155
0
5
Order By: Relevance
“…Normally the phenolic compounds act by scavenging free radical and quenching the lipid peroxidation [28]. As presented here caffeic acid has the ability to scavenge the free radicals [29] and attenuate the lipid peroxidation as indicated by increased levels of enzymic antioxidants in the liver [30].…”
Section: Resultsmentioning
confidence: 73%
“…Normally the phenolic compounds act by scavenging free radical and quenching the lipid peroxidation [28]. As presented here caffeic acid has the ability to scavenge the free radicals [29] and attenuate the lipid peroxidation as indicated by increased levels of enzymic antioxidants in the liver [30].…”
Section: Resultsmentioning
confidence: 73%
“…A number of studies have shown that the caffeic acid and chlorogenic acid present in several plants exhibited hypoglycemic activity and antioxidant properties in experimental animals [29,30,31,32]. The presence of these compounds together with dicaffeoil quinic derivates led us to think that they could be hypoglycemic principles of the decoction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we think that the other components of coffee, besides caffeine, may have positive effects on insulin signaling. Actually, caffeic acid ingestion is reported to significantly reduce the blood glucose and glycosylated hemoglobin levels in C57BL/KsJ-db/db mice (20). Ferulic acid was also shown to reduce blood glucose concentrations in KK-A y mice (21), C57BL/KsJ-db/db mice (22), and streptozotocin-induced diabetic mice (21) and rats (23).…”
Section: Discussionmentioning
confidence: 99%